Impact of PCSK9 on CTRP9-Induced Metabolic Effects in Adult Rat Cardiomyocytes - Rohrbach, Susanne; Li, Ling; Novoyatleva, Tatyana; Niemann, Bernd; Knapp, Fabienne; Molenda, Nicole; Schulz, Rainer (Frontiers in Physiology, 2021)
The adipocytokine adiponectin and its structural homologs, the C1q/TNF-related proteins (CTRPs), increase insulin sensitivity, fatty acid oxidation and mitochondrial biogenesis. Adiponectin- and CTRP-induced signal transduction has been described to involve the adiponectin receptors and a number of co-receptors including the Low density lipoprotein receptor-related protein 1 (LRP1). Since LRP1 is also a target of the proprotein convertase subtilisin/kexin-9 (PCSK9), we investigated the influence of PCSK9 on the metabolic effects of CTRP9, the CTRP with the highest homology to adiponectin. Knockdown of LRP1 in H9C2 cardiomyoblasts blunts the effects of CTRP9 on signal transduction and mitochondrial biogenesis, suggesting its involvement in CTRP9-induced cellular effects. Treatment of adult rat cardiomyocytes with recombinant PCSK9 but not knockdown of endogenous PCSK9 by siRNA results in a strong reduction in LRP1 protein expression and subsequently reduces the mitochondrial biogenic effect of CTRP9. PCSK9 treatment (24h) blunts the effects of CTRP9-induced signaling cascade activation (AMP-dependent protein kinase, protein kinase B). In addition, the stimulating effects of CTRP9 on cardiomyocyte mitochondrial biogenesis and glucose metabolism (GLUT-4 translocation, glucose uptake) are largely blunted. Basal fatty acid uptake is strongly reduced by exogenous PCSK9, but only minor effects were observed on CTRP9-induced fatty acid (FA) uptake or the expression of genes involved in FA uptake and oxidation. In conclusion, PCSK9 treatment influences LRP1-mediated signaling pathways in cardiomyocytes. Thus, therapeutic PCSK9 inhibition may provide an additional benefit through stimulation of glucose metabolism and mitochondrial biogenesis in addition to the lipid-lowering effects. This could be an important beneficial side effect in diabetic or failing hearts which are characterized by impaired mitochondrial function and reduced metabolic flexibility.